Implementation of Complete Systematic Land Registration Program (PTSL) Based on Government Regulation No. 24 of 1997 on Land Registration in the Subang District - Hani Handayani; Rizky Adiyanzah Wicaksono; Amin Purnawan (Jurnal Akta, 2018)
The purpose of this study are to: 1) to investigate the implementation of Complete Systematic Land Registration Program based on Government Regulation No. 24 of 1997 on Land Registration in Subang district. 2) To know the constraints and solutions implementation of Complete Systematic Land Registration Program based on Government Regulation No. 24 of 1997 on Land Registration in Subang district.In this study the authors use research methods socio-juridical / empirical / non-doctrinal where qualitative approach is a way of analysis of the results of research that produces descriptive data analysis, the data stated by the respondent in writing or orally as well as the real behavior, researched and studied as something related intact on Government Regulation No. 24 of 1997 on Land Registration in Subang district.Based on the results of data analysis concluded that: 1) Implementation of Complete Systematic Land Registration Program based on Government Regulation No. 24 of 1997 on Land Registration in Subang district. Implementation of Complete Systematic Land Registration program in the Subang district earring positive influence on the creation of orderly land, particularly against the rule of law and orderly administration of land, which is indicated by the number of parcels of land have been able certified in the land registration process. This will have an impact on the decrease in the number of land disputes, because residents have proof of land ownership (certificate) and the presence of land records are complete.Keywords: Complete Systematic Land Registration Program, Government Regulation No. 24 of 1997 on Land Registration.